2003
DOI: 10.1038/sj.bjp.0705049
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of intestinal dipeptide transport by the neuropeptide VIP is an anti‐absorptive effect via the VPAC1 receptor in a human enterocyte‐like cell line (Caco‐2)

Abstract: 1. Optimal dipeptide and peptidomimetic drug transport across the intestinal mucosal surface is dependent upon the co-operative functional activity of the di/tripeptide transporter hPepT1 and the Na(+)/H(+) exchanger NHE3. The ability of the anti-absorptive enteric neuropeptide VIP (vasoactive intestinal peptide) to modulate dipeptide uptake was determined using human intestinal (Caco-2) epithelial cell monolayers. 2. Uptake of glycylsarcosine (Gly-Sar) across the apical membrane of Caco-2 cell monolayers is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 52 publications
1
33
1
Order By: Relevance
“…It has been reported that PEPT1, a proton-dependent dipeptide transporter, is linked to Na/H exchange in mammalian intestinal epithelial cells to regulate cellular pH (1,2,11,12,28) as well as the activation of other proton-solute cotransporter processes to stimulate Na/H exchange in intestinal epithelial cells (27). Interestingly, colon cancer cells (Caco-2) transfected with SGLT1 immediately upon activation have been suggested to stimulate Na/H exchange.…”
Section: ·30 Smentioning
confidence: 99%
“…It has been reported that PEPT1, a proton-dependent dipeptide transporter, is linked to Na/H exchange in mammalian intestinal epithelial cells to regulate cellular pH (1,2,11,12,28) as well as the activation of other proton-solute cotransporter processes to stimulate Na/H exchange in intestinal epithelial cells (27). Interestingly, colon cancer cells (Caco-2) transfected with SGLT1 immediately upon activation have been suggested to stimulate Na/H exchange.…”
Section: ·30 Smentioning
confidence: 99%
“…Indeed, uptake of dipeptides by the H + /oligopeptide transporter on the apical membrane in Caco-2 cells has been suggested to be indirectly controlled by NHEs, which supply the H + gradient for this peptide uptake mechanism(s) (Thwaites et al, 2002). Hence, this oligopeptide transport system exhibits apparent Na + -dependence in its substrate uptake, and NHE inhibitors hinder uptake of glycylsarcosine (GlySar) in Caco-2 cells (Thwaites et al, 2002;Anderson et al, 2003). Functional modulation by NHE can also occur intracellularly, since NHE can export H + , which is taken up by oligopeptide transporters.…”
mentioning
confidence: 99%
“…Cell culture of Caco-2 cells (passage 105-124) was performed essentially as described previously [12,20,21]. Experiments were performed 14-17 days after seeding and 18-24 h after feeding.…”
Section: Cell Culturementioning
confidence: 99%
“…However, there are differences in the ionic dependence of peptide transport when hPepT1 activity is compared in isolation and in the endogenous situation where hPepT1 is colocalised in the specialised brush-border membrane with a large number and variety of transport proteins involved in transmembrane solute and ion movement. Following heterologous expression in X. laevis oocytes or HeLa cells, PepT1 functions as an H + -coupled, pHdependent, Na + -independent transporter [13,14,16], whereas in intact intestinal tissue preparations dipeptide uptake is also dependent on extracellular Na + [16][17][18][19][20][21]. The apparent Na + dependence of dipeptide uptake is the net result of a reciprocal functional relationship between PepT1 and an apically localised Na + /H + exchanger [20,22,23].…”
mentioning
confidence: 99%
See 1 more Smart Citation